TEKNOLOGI HIJAU: SOLUSI UNTUK PELESTARIAN SUMBER AIR (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2014)
This study aims to determine how these green technologies is a solution to preserve water resources. The research method is literature. The results obtained are: climate change caused by global warming are already being felt its impact in people's lives. If no preventive efforts, the impact of global warming in the future is a very serious threat to the lives of all the creatures on earth. In the face of the impact of Global Warming necessary mitigation efforts and adaptation that involves the community, such as water resource conservation technology with plant biology (bio-park), domestic waste water treatment technology with ecological sanitation (Ecosan), flower garden waste water (waste water garden), sanitation garden (sanita) and the concept of green technology (green tecnology). Green technology is one of adaptation and mitigation of the impact of Global Warming which is in line with the principle of sustainable development (sustainable development). Various Green Technology in the field of preservation of water resources and wastewater treatment has been available to be applied in the construction. Suggestions in this study are: for the government to attempt to campaign for the use of green technology and for the community also can use green technology in order to minimize global warming ranging from the household.Keywords: green technology and conservation of water resources